Proportion of Gestational Diabetes Mellitus among the Pregnant Mothers and Their Socio-Demographic Characteristics Attending ANC Corner at ShaheedZiaur Rahman Medical College Hospital, Bogura - Razia, Sultana; Sarker, Protima Rani; Saha, Ashees Kumar (International Journal of Medical Science and Clinical Research Studies, 2021)
Background: The proportion of Diabetes is becoming more aggregate around the universe, and it is linked to both genetic and environmental causes. Because of the rising prevalence of type 2 diabetes among young people, the number of pregnancies with this problem has increased. Objectives: The aim of the study was to assess the proportion of Gestational Diabetes Mellitus (GDM) among the pregnant mothers and their socio-demographic characteristics. Methods: A hospital based cross-sectional study was carried out and sample size was calculated using the formulae of (n= Z2pq/d2). The calculated sample size was 376 and purposive sampling technique was used for data collection. A semi-structured questionnaire containing socio-demographic and obstetrics details were used as a study tool and an interview schedule was used for data collection. Results: Out of total 369 pregnant 33.33% GDM found within the age group 26-30 years, 24.83% within the age group 16-20 years, 25% within the age group 21-25 years, 10.41% within the age group of 31-35 years, and 10.41% GDM found within the age group more than 35 years. The pregnant women minimum age was 17.00, maximum 40, range 23, mean and SD was 25.69(±5.43) years. Higher rate of GDM present in class (VI – XII) and degree/PG educational qualification and positive family history of diabetes mellitus of pregnant women’s was 40.16%. Highest number of pregnant women diagnosed as a GDM came from Urban as well as 64.58% and lowest number of pregnant women came from rural area 35.4%. Highest number of pregnant women 87.5% and 12.5% pregnant women diagnosed as a GDM reason was overweight and Obese Class- I. The proportion of GDM was 12.76%. When the socio-demographic and obstetrics details of mothers were compared among GDM and normal mothers it was found that there was highly statistically relationship was observed between pregnant women’s diagnosed as a GDM and Types of family, Monthly family Income, Educational qualification of participants, Occupation of participants, BMI while highly statistically relationship was observed in Family history, Abortion, Meal in 24 hours, feel any Sickness, Physically active, GDM in previous pregnancy and Age at first marriage (p=0.000). Conclusions: Frequency of GDM seems alarming in Bangladesh. The findings show that socio-demographic and obstetric factors have an impact on the proportion of GDM.